Catalytic electrochemical water splitting using boron doped diamond (BDD) electrodes as a promising energy resource and storage solution - Al-Abdallat, Yousef; Jumah, Inshad; Jumah, Rami; Ghanem, Hanadi; Telfah, Ahmad (Energies, 2020)
The present study developed a new system of electrochemical water splitting using a boron doped diamond (BDD) electrode in the electrochemical reactor. The new method assessed the electrical current, acidity (pH), electrical conductivity, absorbance, dissipation, and splitting energies in addition to the water splitting efficiency of the overall process. Employing CuO NPs and ZnO NPs as catalysts induced a significant impact in reducing the dissipated energy and in increasing the efficiency of splitting water. Specifically, CuO NPs showed a significant enhancement in reducing the dissipated energy and in keeping the electrical current of the reaction stable. Meanwhile, the system catalyzed with ZnO NPs induced a similar impact as that for CuO NPs at a lower rate only. The energy dissipation rates in the system were found to be 48% and 65% by using CuO and ZnO NPs, respectively. However, the dissipation rate for the normalized system without catalysis (water buffer at pH = 6.5) is known to be 100%. The energy efficiency of the system was found to be 25% without catalysis, while it was found to be 82% for the system catalyzed with ZnO NPs compared to that for CuO NPs (normalized to 100%). The energy dissipated in the case of the non-catalyzed system was found to be the highest. Overall, water splitting catalyzed with CuO NPs exhibits the best performance under the applied experimental conditions by using the BDD/Niobium (Nb) electrodes.
CRIS-Team Scopus Importer:2020-10-30
Keywords: BDD; Boron doped diamond; CuO NPs; Energy storage; Water splitting; ZnO NPs